2021
DOI: 10.1111/trf.16460
|View full text |Cite
|
Sign up to set email alerts
|

Survey to inform trial of low‐titer group O whole‐blood compared to conventional blood components for children with severe traumatic bleeding

Abstract: Background Low‐titer group O whole‐blood (LTOWB) is being used for children with life‐threatening traumatic bleeding. A survey was conducted to determine current LTOWB utilization and interest in participation in a randomized control trial (RCT) of LTOWB versus standard blood component transfusion in this population. Study design and methods Transfusion medicine (TM) directors and pediatric trauma directors at 36 US children's hospitals were surveyed by e‐mail in June 2020. Hospitals were selected by participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Interestingly, the results of this survey of females of childbearing potential are somewhat at odds with the results of a survey of the directors of the transfusion and trauma services at the 30 largest children's specialty hospitals 15 . These medical specialists were asked if they would be comfortable enrolling injured boys and girls of unknown RhD type in a study of RhD‐positive LTOWB versus components for their initial resuscitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the results of this survey of females of childbearing potential are somewhat at odds with the results of a survey of the directors of the transfusion and trauma services at the 30 largest children's specialty hospitals 15 . These medical specialists were asked if they would be comfortable enrolling injured boys and girls of unknown RhD type in a study of RhD‐positive LTOWB versus components for their initial resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the results of this survey of females of childbearing potential are somewhat at odds with the results of a survey of the directors of the transfusion and trauma services at the 30 largest children's specialty hospitals. 15 These medical specialists were asked if they would be comfortable enrolling injured boys and girls of unknown RhD type in a study of RhD-positive LTOWB versus components for their initial resuscitation. While 80% of the responding transfusion medicine directors and 72% of the responding trauma directors would be willing to enroll boys in this study, only 20% of the transfusion medicine directors and 38% of the trauma directors would be willing to enroll girls in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reallocation of D‐negative RBCs away from prehospital use would facilitate the provision of these scarce RBCs to patients who are already D‐alloimmunized, and patients who require antigen‐matched RBC such as sickle cell disease patients for whom alloimmunization could pose dire long term health consequences. A survey of transfusion and trauma services directors at the 30 largest children's specialty hospitals in the United States revealed some reluctance to enroll injured girls of unknown D‐type in a study of D‐positive LTOWB transfusion versus component therapy, consistent with the traditional practice of providing D‐negative blood components in this clinical setting [ 29 ]. However, in a survey of staff at a large American university, 90% of the respondents who were females of CBP indicated that they would accept a lifesaving transfusion even with the knowledge that it could harm future pregnancies [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these risk estimates, a survival benefit of 1% or greater components in this clinical setting [29]. However, in a survey of staff at a large American university, 90% of the respondents who were females of CBP indicated that they would accept a lifesaving transfusion even with the knowledge that it could harm future pregnancies [30].…”
Section: T a B L E 1 Estimation Of Risk Of Harm From Transfusion Of D...mentioning
confidence: 99%
“…5 There have been several recent articles presenting the case that this practice should be reconsidered to ensure optimal trauma care as, due to supply issues, it is difficult to provide group O RhD-negative (ONEG) RBCs in the pre-hospital setting or when using whole blood (WB). [6][7][8][9][10][11][12] The recommendation is that group O RhD-positive (OPOS) RBCs or WB be used in these circumstances since the benefit of transfusion outweighs the harm to a patient of childbearing potential developing anti-D and having a pregnancy affected by HDFN. As in all areas of medicine, it is healthy to thoughtfully debate possible changes in practice with an eye towards evidence and a risk to benefit assessment. In this commentary, we will review our understanding and interpretation of current data supporting the use of pre-hospital transfusion and WB in trauma care (i.e., the benefits) and the current morbidity and mortality related to anti-D HDFN (i.e., the harms).…”
mentioning
confidence: 99%